RUMAH “SAKIT JIWA” (TEATER MODERN) - Suprianda, Andicky; Tulus Handra Kadir (Universitas Negeri Padang, 2026)
This artwork aims to interpret the phenomena and behavior of people in a mental hospital. The creation process involves observation (exploration), improvisation, and formation. The idea for the theatrical work